借鉴新加坡经验 ： 探索实现吉林工业化的新思路 = On the industrialization of Jilin economy : lessons from Singapore experiences - 梁占田 Liang, Zhantian (2008)
Based on economics theories and the successful experience of Singapore's economy, this thesis studies the fundamental strategies and main policies for economics industrialization in Jilin Province.